Kebutuhan Informasi Siswa SMP Negeri 1 Kota Padang melalui Sumber-Sumber Internet - Devi, Intan Masyitha; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2020)
Abstract This paper discusses the information needs of students at SMP Negeri 1 Kota Padang through internet sources. the writing of this paper aims to describe: (1) the individual (personal) information needs of students of SMPN 1 Kota Padang; (2) information needs related to the role of students of SMPN 1 Kota Padang; (3) information needs related to the environment of students of SMPN 1 Padang City. This research uses a descriptive method with a qualitative approach, which is collecting data by observing and interviewing 12 students. Based on the results of research and discussion of data about the information needs of students of SMPN 1 Padang through internet sources, it can be concluded that: the information needs of students of SMPN1 Padang through internet sources, namely: First, individual (personal) information needs, through the internet students can search light reading information (magazines, fiction works such as short stories, novels), health, travel, culinary, skills. These needs are used to break away from fatigue everyday. Secondly, information needs related to roles, through the internet students can meet information needs to complete school work, meet information needs about self-development, and information needs about life motivation, ideals. These are related to their social roles as students. Third, the need to find out the latest conditions and situations regarding the surrounding environment (local) cultural conditions, physical / natural conditions and the place of residence they live in, especially Padang City. This is because in their individuals there are social needs (social needs) that must be met.Keywords: information needs; students; internet sources